Spatial distribution, biomass and size structure of Ctenodiscus australis (Echinodermata: Asteroidea) in shelf-break areas, Argentine - Escolar, Mariana (2011)
Ctenodiscus australis is a common sea star in the Argentine Continental Shelf. Nevertheless, information about its population parameters lacks. We investigated the spatial distribution, biomass and size structure of this sea star through a spatial and temporal scale in Patagonian scallop (Zygochlamys patagonica) fishing grounds associated with the shelf-break front in the Argentine Sea. The sea star C. australis was very frequent in the Patagonian scallop management units (MUs) analyzed and reached 100% presence in most of them. The species biomass showed latitudinal differences with the highest values in northern MUs during the period 2002-2005, probably related to the organic content in sediments. The comparative study in two areas subjected to different fishing effort in the same MU showed the highest biomass of this sea star in the area with low fishing effort. The size frequency distribution of C. australis suggests a low or sporadic recruitment and slow growth. Differences in the median size were found among MUs but these cannot be attributed to fishing effort.